‘Bureaucracy within representative government: an overview among UiTM Melaka lecturers’/ Mohd Ab Malek Md Shah, Jeniwaty Mohd Jody and Nor Azira Ayob - Md Shah, Mohd Ab Malek; Mohd Jody, Jeniwaty; Ayob, Nor Azira (Research Management Institute (RMI), 2012)
Significantly, the bureaucracy within representative government is truly vital in designing the pathway of the administration system accordingly. Regarding to Mill’s theory, he opined that the basic aim of each government is to strive for the empowerment of aristocrats, elimination of biasness; as well as for the emancipation of women, workers and slaves. In addition, he also encouraged such public participation in the government sector; on the condition that such candidate should be well – equipped with a good educational background in order to protect the conduciveness of political climate and examine the suitability of the bureaucracy within representative government of the country. Previously, it has been argued that politics indeed is influenced by the administrative system of each government holistically. Yet, John Nalbandian (1994) claimed that both administration and politics are actually sharing a reciprocal relationship between each of them as a whole. On the other hand, each of them has particular vision and mission respectively. Consequently, both politics and administration system which refer to a local government must have reached at a consensual agreement in delivering good services to the public at large towards good governance. Thus, it is hoped that this writing would become a cornerstone and platform for discussion in enhancing the effectiveness of local government in Malaysia which eventually create an awareness among UiTM Cawangan Melaka lecturers towards this concept of bureaucracy within representative government